2005
DOI: 10.1007/s00586-004-0843-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of single-level, total disc arthroplasty on sagittal balance parameters: a prospective study

Abstract: A prospective radiographic study of the influence of total disc replacement on spinal sagittal balance. The goal of this study was to prospectively determine the effect of a single-level, total disc replacement on the sagittal balance of the spine, especially on sacral tilt (ST), pelvic tilt (PT), and lumbar lordosis. It has been shown that lumbar fusion may deleteriously alter the sagittal balance of the spine, including a decrease in the ST and lumbar lordosis. Clinically, postfusion pain has been shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 20 publications
7
43
0
1
Order By: Relevance
“…A disc prosthesis in L5-S1 appeared more suitable for backs with a lower sacral slope. Backs with a higher sacral slope produce increased shear constraints and reduce this regulator role due to reduced mobility of the prostheses [10]. It will be possible to vary the different sizes/heights and angles of prostheses in order to optimise their effect on L5-S1, although in practice this effect appeared very limited and random [9].…”
Section: Discussionmentioning
confidence: 99%
“…A disc prosthesis in L5-S1 appeared more suitable for backs with a lower sacral slope. Backs with a higher sacral slope produce increased shear constraints and reduce this regulator role due to reduced mobility of the prostheses [10]. It will be possible to vary the different sizes/heights and angles of prostheses in order to optimise their effect on L5-S1, although in practice this effect appeared very limited and random [9].…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary aims of TDR is to preserve motion and thereby ultimately avoid stress and degeneration of the adjacent segment. Radiographic studies have demonstrated maintained physiological sagittal and spinopelvic alignment following TDR [5,10,33,61]. It has therefore been hypothesized that the above-mentioned fusion-related negative side effects and post-fusion pain patterns could be avoided with TDR.…”
Section: Discussionmentioning
confidence: 99%
“…In a radiographic study with 35 patients, LeHuec et al [33] concluded that the Maverick prosthesis had enough freedom of motion to maintain the natural sagittal and spinopelvic balance needed to prevent potential undue stress on the muscles and the sacroiliac joints. However, this is the first study to demonstrate that the lumbar facet and sacroiliac joints are a similarly frequent cause of post-operative pain.…”
Section: Diagnostic Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Total disc replacement (TDR) is one such technique and was developed to avoid the negative effects of arthrodesis by preserving function of the motion segment. The theoretical mechanism of pain relief is based on a combination of complete excision of the painful disc and restoration or improvement of segmental load transfer, sagittal balance and motion [5,14] hoping that this will improve both short-and long-term results. Reduced degeneration of the adjacent spine, as indicated by an in vitro study [6] may be an advantage, but still needs to be proven in prospective studies.…”
Section: Introductionmentioning
confidence: 99%